Human Nature, Sociobiology and Counselling - Lang, William A.; West, Lloyd W. (Canadian Journal of Counselling and Psychotherapy, 2012)
Assumptions about human nature play an important role in the formation of counselling theories. Sociobiology suggests that much of our basic psychological makeup is genetically determined and has evolved by means of natural selection. The sociobiological picture of human nature challenges the assumptions that human goodness is innate and that human behavior is easily modified by reinforcement. Rather, sociobiology suggests that biologically based human predispositions will often conflict with the legal and moral requirements of modern life and that resolving this conflict will not be easy. Accordingly, sociobiology provides support for the direct teaching of moral values and social skills to compensate for the vestigial predispositions which impede self and social enhancement. Sociobiology, thus, may serve as the cornerstone of a rationale for the role of counsellor as educator.